Characteristics Of Therapeutic Drug Classes In Patients With Mental Illness At The Kota Timur Public Health Center, Gorontalo In 2024 - Sabrina, Putri; Tuloli, Teti Sutriyati Tuloli Sutriyati; Paneo, Mohamad Aprianto; Rasdiana, Nur; Manno, Mohammad Reski (Jambura Nursing Journal, 2025)
Mental illness is a pressing global health issue due to its extensive impact on individuals, families, and society. Mental disorders such as depression, anxiety, and schizophrenia not only affect a person's psychological condition but also their quality of life, productivity, and socio-economic well-being. The urgency of addressing mental illness continues to increase with its high prevalence and the persistent stigma in society. Limited understanding and restricted access to mental health services remain major challenges in managing mental disorders. Therefore, studying the characteristics of therapeutic drug classes in patients with mental illness is crucial for understanding drug usage patterns and therapy effectiveness. This study aims to identify the characteristics of therapeutic drug classes used in patients with mental illness at the Kota Timur Public Health Center, Gorontalo. This study employs a descriptive observational design with a retrospective data collection method. The data are obtained from secondary sources, specifically the medical records of 35 patients with mental illness. The data are processed using Excel and analyzed with SPSS version 26. The findings indicate that mental illness patients are predominantly male (57%), with the highest incidence occurring in the age range of 34-46 years (43%). The area with the highest incidence of mental illness is Padebuolo (23%), and the majority of patients are in the maintenance phase of treatment (88%). Schizophrenia is the most common mental illness, accounting for 71% of cases. The most frequently used antipsychotic drugs are risperidone 2 mg 2x1 (28rwalozapine 25 mg 2x½ (25%), chlorpromazine 100 mg 2x (6%), and hamo anticholinergic drugs, trihexyphenidyl is the mostru diazepam 2 mg 1×1 accounted for 3%.